2007
DOI: 10.1128/aac.01498-06
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of the Anti-Human Immunodeficiency Virus Agent 1-(β-d-Dioxolane)Thymine in Rhesus Monkeys

Abstract: The discovery of the antiviral activity of ␤-D-dioxolaneguanine (DXG) and its prodrug amdoxovir (DAPD) against zidovudine (AZT)-and lamivudine-resistant mutants (19) prompted us to revisit D-DOT to explore the activity against mutant viruses, since D-DOT also contains the dioxolane sugar moiety (see Fig. 1). D-DOT demonstrated potent activity in human PBM cells against lamivudine-resistant (M184V) (EC 50 ϭ 0.088 to 0.2 M), tenofovir-resistant (K65R) (EC 50 ϭ 0.21 M), didanosine-resistant (L74V) (EC 50 ϭ 0.33 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Understanding the pharmacokinetic profile of a drug is important for estimating the rate and extent of absorption and elimination 18‐21 . Of particular significance are data associated with drug exposure, drug half‐life, systemic distribution and clearance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the pharmacokinetic profile of a drug is important for estimating the rate and extent of absorption and elimination 18‐21 . Of particular significance are data associated with drug exposure, drug half‐life, systemic distribution and clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the pharmacokinetic profile of a drug is important for estimating the rate and extent of absorption and elimination. [18][19][20][21] Of particular significance are data associated with drug exposure, drug half-life, systemic distribution and clearance. Moreover, in vitro ADM data provide additional information for the analysis and interpretation of in vivo data.…”
Section: Pharmacokinetic Parametersmentioning
confidence: 99%
“…In the search for effective antivirals, research centers have screened compounds which previously demonstrated to possess antiviral activity against other pathogens for their therapeutical potential against ZIKV infection [ 40 ]. As an example, nucleoside analogues showed to inhibit the viral replication of the herpes simplex viruses 1 and 2 (HSV-1 and HSV-2) [ 80 ], cytomegalovirus (CMV) [ 81 ], hepatitis B virus (HBV) [ 82 ], human immunodeficiency virus (HIV) [ 83 , 84 , 85 , 86 ], and hepatitis C virus [ 87 ].…”
Section: Therapeutical Potential Of Anti-zikv Moleculesmentioning
confidence: 99%